Solar Energy as an Alternative to Conventional Energy in Gaza Strip: Questionnaire Based Study - Hala El-Khozondar; Fady El-Batta (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Solar energy system is currently used in Gaza Strip as a replacement source or complementary source to the traditional source of energy. However, using solar energy is happening without any planning or clear vision. Gaza Strip is supplied by electricity from three main sources: Egypt, Israel, and local electricity plant in GazaStrip. However, most of the time, one or two or sometimes the three sources are cut due to the po-litical situation keeping Gaza Strip under darkness most of the time.This work aims to study the use of solar energy as an alternative to conven-tional energy in Gaza Strip: Questionnaire based study. The study has been implemented on local institutions(governmental, private and public) in Gaza Strip. To verify its aim, the authors distributed a questionnaire to a sample comprised 13 institutions where 53.8% of the sample are public institutions, 23.1% are government institutions and 23.1% are private in-stitutions.The institutions in the sample do not use solar energy as a full replacement. The researchers analyzed the collected data using SPSS (Statistical Package for the Social Sciences), which include descriptive statistics (the percentage, the mean, the standard deviation and weighted arithmetic mean); Pearson correlation coefficient; Cronbach's Alpha coefficient; Spearman-BrownSpilt Half; and One Samples t test. Results indicate that the local institutions chose to use solar energy due to the fact the system is environmentally safe and it is available in the market. Moreover, results show that the institutions prefer to use solar energy re-gardless to the price. This might be explained by the fact that solar sys-tems are the safest replacement to the current systems.Results also did not depend on the institutions’ attributes (institution type, the year at which the institution started using solar energy, the ratio of relying on solar power as an energy source). We recommend to use solar energy system to help overcome the current problem of electricity shortage and to extend the study to include other sectors in the local society.